2017
DOI: 10.1186/s12885-017-3763-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival time following resection of intracranial metastases from NSCLC-development and validation of a novel nomogram

Abstract: BackgroundBrain metastases (BM) from non-small cell lung cancer (NSCLC) are the most frequent intracranial tumors. To identify patients who might benefit from intracranial surgery, we compared the six existing prognostic indexes(PIs) and built a nomogram to predict the survival for NSCLC with BM before they intended to receive total intracranial resection in China.MethodsFirst, clinical data of NSCLC presenting with BM were retrospectively reviewed. All of the patients had received total intracranial resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…[16] In our study, DS-GPA was not statistically significant for OS, while it was statistically significant in other studies. [15,43,38] Modified Lung-Specific GPA improved the OS of patients with brain metastasis from lung cancer, similar to our study. [17] Limitations of the Study Our study has several limitations.…”
Section: Clinical Characteristics (N=95) Cox Regression P-value Hr 95supporting
confidence: 90%
See 2 more Smart Citations
“…[16] In our study, DS-GPA was not statistically significant for OS, while it was statistically significant in other studies. [15,43,38] Modified Lung-Specific GPA improved the OS of patients with brain metastasis from lung cancer, similar to our study. [17] Limitations of the Study Our study has several limitations.…”
Section: Clinical Characteristics (N=95) Cox Regression P-value Hr 95supporting
confidence: 90%
“…[37,6] Ji et al showed that overall survival was increased in patients with favorable KPS on univariate analysis and multivariate analyses. [38] In our study, OS was increased in patients with favorable KPS, control of the extracranial disease, controlled primary tumor as reported by Gao. [39] Our series also matches with previous reports that have demonstrated improved median OS with better control of the extracranial disease.…”
Section: Clinical Characteristics (N=95) Cox Regression P-value Hr 95supporting
confidence: 81%
See 1 more Smart Citation
“…In our subject-related areas, current researches included prognostic analysis of tumor brain metastasis [ 34 ], survival analysis of non-small cell lung cancer (NSCLC) after surgical resection [ 33 ], and prognosis of NSCLC brain metastasis after surgery [ 35 , 36 ], but there had not been a LCSBM prognostic prediction model. Therefore, it was necessary to examine prognostic risk factors for such patients and establish a reliable prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that KPS was related to OS in this patient population, and this is supported by other studies. A study that aimed to predict the survival of patients with NSCLC and brain metastasis showed that KPS at diagnosis of brain metastasis was an independent predictor of survival (32). Another study showed that a KPS of 90% vs. 70-80% was a significant prognostic factor after radical treatment for oligometastatic NSCLC (33).…”
Section: Discussionmentioning
confidence: 99%